Analisis Pengaruh Pertumbuhan Ekonomi , Kemiskinan Dan Pengangguran Terhadap Indeks Pembangunan Manusia (IPM) Di Wilayah Subosukawonosraten - Nurhaini, Rela Setiaji; , Ir. Maulidyah Indira Hasmarini, MS. (2016)
Human development is a process of development that aims to be able to have more choices, particularly in income, health and education. One criterion can be seen through the Human Development Index. The purpose of this study was to analyze how the effect of economic growth, poverty, unemployment, of the human development index. The analytical method used in this research using panel data regression analysis of the effects of random (Random Effect Method / REM). The results of this study indicate that economic growth is positive and significant effect on the Human Development Index (HDI), poverty and negative and no significant effect on the Human Development Index (HDI), the unemployed don't affect significant on the Human Development Index (HDI) on the Human Development Index (HDI) in the region SUBOSUKAWONOSRATEN.